Incidence of two caterpillar species (Lepidoptera: Crambidae) and injuries caused by them in sweet basil grown in Seropédica County, RJ - Aguiar-Menezes, Elen de L.; Fernandes, Vinicius J.; Menezes, Eurípedes B. (Entomological Communications, 2021)
Ocimum basilicum L. (Lamiaceae) is one of the most popular herbs in the world, given its aromatic, medicinal and insecticidal properties. Its leaves are rich in essential oils, as well as the plant part with the highest economic value in this species. The aims of the current study are to identify the causative agent of injuries observed in sweet basil plants grown in Seropédica County, RJ (Brazil), as well as to feature both their feeding behavior and injuries caused by them. The herein investigated injuries were caused in sweet basil stems and leaves by caterpillars, which were collected with the leaves and grown in laboratory until they reached the adult stage. Two lepidopteran species belonging to family Crambidae were identified, namely: Hyalorista opalizalis (Guenée, 1854) and Pyrausta phoenicealis (Hübner, 1818); approximately 73% of adult individuals obtained in laboratory belonged to the first species. Caterpillars belonging to both species have caused similar injuries to O. basilicum plants. Injuries were featured by the sectioning of stems whose leaves were bundled with silk threads and formed a shelter, where caterpillars ate the leaf limb in. The current study also recorded O. basilicum plants used as hosts by P. phoenicealis insects, for the first time.